Management regimes within syntaxa of semi-natural grasslands in west Bulgaria - Velev, Nikolay; Vassilev, Kiril (Hacquetia, 2015)
This study focuses on mesic and xeric grasslands of mostly secondary origin, and that are influenced by human activity. Mesic grasslands are traditionally used for hay-making, and xeric ones for pastures. Over the last 20 years, livestock farming in Bulgaria has significantly declined so that less grass is needed. Many types of grasslands are no longer used and lots of abandoned fields can be found nowadays in Bulgaria. The analyses in this study are based on 868 relevés collected on xeric and mesic grasslands according to the methodological approach of Braun- Blanquet. As a result, five alliances within two classes are recognized: the class Festuco-Brometea, represented by three alliances, namely Cirsio-Brachypodion pinnati, Chrysopogono-Danthonion calycinae and Festucion valesiacae, and the class Molinio-Arrhenatheretea, represented by two alliances, namely Arrhenatherion elatioris and Cynosurion cristati. The majority of the managed grasslands are situated in close proximity to settlements. Most of the abandoned areas (30%) are found within Cirsio-Brachypodion alliance. These grasslands are characterized by the highest values of total cover of vegetation. They are located in the most distant and least accessible areas. If use is not resumed, all the abandoned grasslands will be under threat of extinction in the near future. At the same time, many arable lands have been abandoned and turned into grasslands by the processes of secondary succession.